(untitled) (Research, Society and Development, 2020)
The Pantanal wetland Mato Grosso, Brazil is among the largest floodplains in the world, with a mosaic of different habitats and rich aquatic and terrestrial biota. The habitat mosaics are found in the Chacororé and Sinhá Mariana lake System. These parental lakes of the Cuiabá River, a left tributary of the Upper Paraguay River, are known for their aquatic productivity and scenic beauty. The characteristics of these lakes and their floodplains are showed through the difference between their waters, the diversity of the aquatic macrophytes communities, fish communities and aquatic birds. Our study looked at changes in limnological variables as well as diversity of aquatic birds, during high water or flooded phase; medium water or receding phase; and the low water or dry phase. We used a temporary small lagoon in the floodplain of this system as our study area. The flood pulse is the main ecological factor affecting the Pantanal; it modifies ecological process and species composition. The water depth decreases during the season, decreasing electrical conductivity, dissolved phosphate and nitrate, water transparency, dissolved oxygen and biomass of aquatic macrophyte; and increasing calcium, total phosphorus and total nitrogen. We also observed increase in species richness and abundance of aquatic birds during the receding phase. Results show that the number of species (density) of aquatic birds increased from 10 to 30 species and the numbers of individuals from 40 to 936. The maximum richness and abundance of aquatic birds was registered during the receding phase.